Sistem Layanan Terbuka di Perpustakaan SMP N 3 X Koto - Muhamad Arif (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2022)
This research is motivated by several problems related to the open service system found in the library of SMP N 3 X Koto. In terms of the open service system contained in the library, it has actually been implemented optimally, but there are still things that need to be improved so that open services can improve even better. The aims of the research are (1) to find out how the open service system at SMPN 3 X Koto is. The research method used is qualitative. The data sources that were determined were the head of the library, library staff, and students. Techniques and data collection through interviews, observation, and documentation. The suggested data analysis according to Huberman is data collection, data reduction, data presentation, and verification or drawing conclusions. Based on the results of this study, (1) The open service system in increasing students' reading interest at SMPN 3 X Koto has been carried out well in accordance with the provisions, namely: Users can go directly to the shelves to take collections, collections found can be read on the spot or borrowed to take home, if you want to borrow to take home you can go directly to the circulation service desk so that the open service system is able to increase students' reading interest.